SERVICE QUALITY MANAGEMENT DALAM MENINGKATKAN PENDAPATAN USAHA PENJAHIT ROSDIATI KOTA JAMBI - Vinesha Amanda; Ahsan Putra Hafiz (ICONS: Islamic Economics Journal, 2026)
This research aims to analyze the implementation of the Service quality model and Islamic values in service management at a home-based tailoring business owned by Mrs. Rosdiati in Jambi City. Operating since 2018, this microenterprise exemplifies how quality service can be harmonized with Islamic business ethics. The Service quality model developed by Parasuraman, Zeithaml, and Berry serves as the main analytical framework, consisting of five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Field observations and interviews reveal that these dimensions are clearly reflected in the daily operations of the business. The tailoring shop maintains a neat and organized appearance (tangibles), delivers consistent and reliable services (reliability), responds quickly to customer requests (responsiveness), offers professional and trustworthy interactions (assurance), and shows genuine concern for customers‟ needs and conditions (empathy). Furthermore, this study incorporates Islamic values such as ihsan (excellence), maslahah (benefit), honesty, and accountability into the business operations. Mrs. Rosdiati adheres to principles of transparency and integrity, viewing her work as both a livelihood and a form of worship to seek blessings (barakah).